(3GdhLjR aj EOGQI GdehGQO GdHTQjI (B/s - (3GdbQjhJj, eMeO bGSes ((3YeGf(B: s (3OGQ hGFd(B, s, 2009)
(3GOGQI GdehGQO GdHTQjI , JMdjd GdYed hhUa h JUfja h Jbjje GdhXGFa , JNWjW hGSJbWGH h GNJjGQ GdehGQO GdHTQjI , JOQjH GdehGQO GdHTQjI , Jbjje GdGOGA , GdQhGJH h GdCLhQ h GdJYhjVGJ , JNWjW GdeSGQ GdhXjaj , TDhf GdJQbjI h GdJSQjM GdeDbJ h JfRjd GdOQLI h GdaUd ef GdYed , YdGbGJ GdYed , UjGfI GdehGQO GdHTQjI h JCejf XQha GdCeGf h GdSdGeI dgG(B.s
(3eQGLY (B: (3dcd aUd eQLY ; eQGLY U(B.301s
Keywords: (3EOGQI GdCaQGOs; (3Gdbhi GdYGedIs; (3GdehGQO GdHTQjIs